Variation under Nature - Charles Darwin (The Origin of Species, 2011)
Variability—Individual differences—Doubtful species—Wide ranging, much diffused, and common species vary most—Species of the larger genera in any country vary more than the species of the smaller genera—Many of the species of the larger genera resemble varieties in being very closely, but unequally, related to each other, and in having restricted ranges. in each country vary more frequently than species, vary most—Species of the larger genera in each Before applying the principles arrived at in the last chapter to organic beings in a state of nature, we must briefly discuss whether these latter are subject